Nurses’ justifications for morally courageous acts in ethical conflicts: A narrative inquiry - Pajakoski, Elina (Nursing ethics, 2025)
Background: Moral courage is defined as the courage to act in ethical conflicts based on individual or professional values despite the personal risks involved. Nurses justify their decisions to act morally courageously as part of their ethical decision-making.Objective: To describe registered nurses’ justifications for acting morally courageously, or not, in ethical conflicts where they needed moral courage.Research design: A narrative inquiry with a holistic content approach was used. Individual, in-depth interviews were conducted in January–February 2023. The data were analysed using holistic content analysis.Participants and research context: Fourteen registered nurses with experience in situations where they needed moral courage participated. The nurses came from the somatic, palliative, mental health, and substance abuse care fields in Finland.Ethical considerations: Good scientific practice was followed. Ethical approval was obtained before data collection from the university’s ethics committee.Findings: The nurses needed moral courage in ethical conflicts with patients present and between professionals. Individual responsibility, professional ethics, and emotions were identified as bases of nurses’ justifications for morally courageous acts. The justifications for acting morally courageously, or not, had individual, contextual, and organisational perspectives. Morally courageous acts included starting a discussion about the conflict with other professionals and reporting the situation in writing within one’s organisation.Discussion and conclusions: The identified bases and perspectives of justifications illustrate the complexity of nurses’ decision-making in ethical conflicts, either leading to morally courageous acts or not. These results can inform nursing practice and research in developing processes to strengthen nurses’ moral courage and examining relationships between moral courage and other concepts, such as moral resilience.